Melatonin and Rapamycin Attenuate Isoflurane-Induced Cognitive Impairment Through Inhibition of Neuroinflammation by Suppressing the mTOR Signaling in the Hippocampus of Aged Mice - Yuan, Hui; Wu, Guorong; Zhai, Xiaojie; Lu, Bo; Meng, Bo; Chen, Junping (Frontiers in Aging Neuroscience, 2019)
Melatonin exerts neuroprotective effects on isoflurane-induced cognitive impairment. However, the underlying mechanism has yet to be elucidated. The present study sought to determine if melatonin confers its beneficial effects by acting on mTOR, and it attenuates the neuroinflammation in the hippocampus of the aged mice. A total of 72 male C57BL/6 mice, 16-month-old, were randomly and equally divided into six groups: (1) the control group (CON); (2) the rapamycin group (RAP); (3) the melatonin group (MEL); (4) the isoflurane group (ISO); (5) the rapamycin+ isoflurane group (RAP+ISO); (6) the melatonin+ isoflurane group (MEL+ISO). RAP, RAP+ISO, MEL, MEL+ISO groups received 1 mg/kg/day mTOR inhibitor rapamycin solution or 10 mg/kg/day melatonin solution, respectively, intraperitoneally at 5:00 p.m. for 14 days consecutively. Mice in the CON and ISO groups were administered an equivalent volume of saline. Subsequently, ISO, RAP+ISO and MEL+ISO groups were exposed to inhale 2% isoflurane for 4 h, The CON, RAP and MEL mice received only the vehicle gas. Then, the memory function and spatial learning of the mice were examined via the Morris water maze test. mTOR expression was detected via Western blot, while the concentration of inflammatory cytokines TNF-α, IL-1β, IL-6 and that of melatonin was quantified with enzyme-linked immunosorbent assay. Melatonin and rampamycin significantly ameliorated the isoflurane-induced cognitive impairment and also led to a decrease in the melatonin levels as well as the expression levels of TNF-α, IL-1β, IL-6, and p-mTOR in the hippocampus. In conclusion, these results showed that melatonin and rampamycin attenuates mTOR expression while affecting the downstream proinﬂammatory cytokines. Thus, these molecular findings could be associated with an improved cognitive function in mice exposed to isoflurane.